1983
DOI: 10.1079/bjn19830148
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of nitrogen into rumen bacterial fractions of steers given protein- and urea-containing diets. Ammonia assimilation into intracellular bacterial amino acids

Abstract: 1. Experiments were carried out in vivo to investigate the pathways of ammonia incorporation into rumen bacteria, bacterial fractions and free amino acids within the bacteria.2. Steers were alternately given two isoenergetic, isonitrogenous diets containing the nitrogen mainly as either urea or decorticated groundnut meal (DCGM). At the end of each period on a given diet, a solution of l5NH,C1 was infused into the rumen and samples of rumen contents were removed at 2, 10, 20 and 90 min and 5, 10 and 24 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…The response of GDH to AA supplementation, probably for the same reasons discussed above for GS. The ADH is another major enzyme involved in ammonia assimilation, and forms alanine by amination of pyruvate, under conditions of excess soluble carbohydrate and rumen ammonia (Blake et al, 1983). Alanine, serine and NADPH could inhibit the aminating reaction of this enzyme, but ammonia could induce ADH (Aharonowitz and Friedrich, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The response of GDH to AA supplementation, probably for the same reasons discussed above for GS. The ADH is another major enzyme involved in ammonia assimilation, and forms alanine by amination of pyruvate, under conditions of excess soluble carbohydrate and rumen ammonia (Blake et al, 1983). Alanine, serine and NADPH could inhibit the aminating reaction of this enzyme, but ammonia could induce ADH (Aharonowitz and Friedrich, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that nitrogen from groundnut meal is used more efficiently by rumen microbes than urea, which agrees with growth trials conducted simultaneously on bulls.Certains travaux ont montré que la synthèse microbienne était plus importante à partir d'acides aminés provenant de protéines dégradables que de l'ammoniaque issue d'azote uréique (Blake et al, 1983 …”
unclassified
“…Certains travaux ont montré que la synthèse microbienne était plus importante à partir d'acides aminés provenant de protéines dégradables que de l'ammoniaque issue d'azote uréique (Blake et al, 1983 …”
unclassified
“…reported that a deficiency of methionine and phenylalanine may limit bacterial growth on dieta low in protein and high in RPR. Similarly, Blake et al (1983) found that net bacterial #ynth##i# waa aignifioantly greater vith a natural protein source than with urea diets.…”
Section: Animal Performancementioning
confidence: 99%
“…Amino groupa are then tranaferred to other auitable carbon akeletona for the formation of AA which together with preformed compounda, are uaed in protein and nucleic acid ayntheaia. The eozymee required for the firat atagea of euch a echeme have all been identified in mixed rumen bacteria (Falmquist and Baldwin, 1966;Chalupa et al, 1970;Brfle et al, 1977;Blake et al, 1983) and a variety of aechaniama, acme following established pathway# and others uaing less common routes, h*ve been identified ss providing the carbon ekelet<m# for AA synthesis (Allison, 1969;Emmanuel and Nillgan, 1972;Kristensen, 1974;Bauer et al, 1975).…”
Section: Kechaniaa Of Ammonia-# Fixation By Bwxen Bacteriamentioning
confidence: 99%